The diakonia of Practical Theology to the alienated in South Africa in the light of 1 Peter - Breed, Gert (2014)
This article investigates the role that Practical Theology can play in addressing the problem of alienation amongst the people of South Africa. The investigation is conducted from the viewpoint of the biblical concept of diakonia (service work). This concept as well as the content of Practical Theology as it is found in the first letter of Peter is investigated with the purpose of elucidating the diakonia of Practical Theology with regard to alienation. Four questions are answered in the article:• What may some of the reasons why people in South Africa experience alienation be?• What significance do the results of the most recent research into the diakon word group have for the diakonia of Practical Theology?• What insight can be gained from 1 Peter into the diakonia of Practical Theology for people who may be experiencing alienation in South Africa?• What should the diakonia of Practical Theology in the light of 1 Peter be for people who experience alienation? Intradisciplinary and/or interdisciplinary implications: This article addresses the issue of alienation. This is an issue that also falls within the research field of sociology and psychology. This article wants to make a contribution from a biblical perspective using the exegesis of a New Testament letter (1 Pt) with the focus on 1 Peter 4:10 and the use of the diakon word group in the letter. The article thus also operates on the research field of New Testament Theology. The results of the exegesis are used to give guidelines for the diakonia of Practical Theology in South Africa. The article challenges the way some research in Practical Theology is done, not using the Bible as reference point, thus making the distinction between Practical Theology and sciences like sociology and psychology indistinct.
Keywords: 1 Peter; Practical Theology; South Africa; Alienation; chrarismata; Diakonia; Ministry; Suffering